Pathophysiology and Management of Cerebral Venous Thrombosis - Morais, Mariana B.; Aguiar de Sousa, Diana (Hämostaseologie, 2025)
Cerebral venous thrombosis (CVT) is a less common type of stroke that can occur across all age groups but predominantly affects children and young adults. Diagnosis is often challenging due to the nonspecific and variable clinical presentation. The disease course is heterogeneous, with CVT-related parenchymal lesions developing in approximately 50 to 60% of cases. Despite some advancements, significant gaps persist in understanding the pathophysiology of CVT, including the mechanisms underlying brain injury. Anticoagulation is the cornerstone of CVT treatment, but strategies targeting secondary mechanisms of parenchymal damage are still lacking. Here, the current state of the field is briefly reviewed, with the aim to introduce a wide audience (neuroscientists and clinicians alike) to the disease and inform clinical practice and future research.
Keywords: CVT; thrombosis; pathophysiology; parenchymal brain lesion; stroke